2021
DOI: 10.1002/mp.15258
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and experimental validation of a robust hybrid direct aperture optimization approach for mixed‐beam radiotherapy

Abstract: The objectives of the work presented in this paper were to (1) implement a robust-optimization method for deliverable mixed-beam radiotherapy (MBRT) plans within a previously developed MBRT planning framework; (2) perform an experimental validation of the delivery of robust-optimized MBRT plans; and (3) compare PTV-based and robust-optimized MBRT plans in terms of target dose robustness and organs at risk (OAR) sparing for clinical head and neck and brain patient cases. Methods: A robust-optimization method, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…As all apertures were delivered at standard SAD, no intra‐fraction couch translation was required. This is in contrast to previous MBRT studies that have all reported the use of shortened SSD setups for deliveries of electron apertures 20–26,31 …”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…As all apertures were delivered at standard SAD, no intra‐fraction couch translation was required. This is in contrast to previous MBRT studies that have all reported the use of shortened SSD setups for deliveries of electron apertures 20–26,31 …”
Section: Discussioncontrasting
confidence: 61%
“…For all patients, MBRT plans had either significantly lower or equivalent doses to normal tissue and bone. Being deliverable on current state‐of‐the‐art linacs without the use of electron applicators 26,31 or shortened SSD, 41 MBRT offers significant dosimetric benefits at reduced logistical cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heng et al 15 demonstrated the use of an ionization chamber and film dosimetry to perform PSQA for MBRT plans on a PMMA phantom and a Solid Water phantom. Heath et al 16 suggested the possibility of using log file-based dose calculation and EPID measurement for evaluating the delivery accuracy of MBRT. However, to our knowledge, no prior studies have examined the use of commercial QA devices for MBRT plan verification.…”
Section: Introductionmentioning
confidence: 99%